СOMPOSITION IMAGE REGISTRATION USING PICTURE COLOR DISPERSION - Peleshko, D. D.; Kustra, N. O.; Shpak, Z. Y. (Radio Electronics, Computer Science, Control, 2011)
The authors have developed the method of one-type images centering based on solution of the problem of image topology space almost-factorization with further constriction of the space by solving the problem of correlation maximum search. The almost-factorization problem is solved by introduction of semimetrisc relative to image topology elements color dispersion.